Dramatyczność kolorów historii - Kosicka-Pajewska, Aleksandra (Przestrzenie Teorii, 2021)
The drama of Katyń. The theory of colors, Julia Holewińska based on Józef Czapski’s Old Bielsko Memories, although largely processed. The protagonist of the play is Józef Czapski, a painter-capist, writer, intellectual, prisoner of Starobielsk, Pawliszczew Boru, Griazowiec, who builds his paintings in the performance with colors. The setting for these events is Kozielsk, where the artist was not held, which proves that this is not Czapski’s biography, nor is it a documentary account of camp life. The playwright, on the basis of a harsh and humiliating reality, showed human sensitivity. In Holewińska’s drama, Czapski acts as a guide through the camp experience through the eyes of a colorist. In each sequence, the artist expresses his view of color in art. There are two more allegorical characters in the drama: Our Lady of Kazan, who embodies three beings: Our Lady of Kazan (The Blessed Virgin of Kazan) – as the sacred, the real pilot Janina Lewandowska, and femininity in general. The second allegorical figure is the great Katyń liar, who personifies the whole apparatus of repression and oppression of the NKVD. The background for the conversations between these characters is a two-person choir – one out of a thousand and the Second of thousand. Art of Katyń. The theory of colors is devoted to painful historical events, despite the fact that it is subject to various playwriting procedures, it is moving in its meaning.